UJI KARAKTERISTIK BAHAN BAKAR ALTERNATIF HASIL PENGOLAHAN LIMBAH SAMPAH PLASTIK DENGAN METODE PIROLISASI BERTINGKAT - Baride, La Baride; Achmad , Muhamad Iqbal; Tasman (Jurnal Rekayasa Mesin, 2024)
This study aims to determine the characteristics and quantity of oil produced from first and second level pyrolysis. The method in this research is an experiment with a pyrolysis tool designed in two levels. The advantage of this pyrolysis tool compared to other pyrolysis tools is that it is expected to produce two fuels with different physical and chemical properties. The results of the study showed that for the first level of pyrolysis PP plastic, 855.7 grams of oil was produced with the following characteristics: density @15°C = 754 kg/m³, final boiling point = 264.9°C, distillation @200°C = 71.8% v/v. while in the second level pyrolysis for the PP plastic type, it produces 138.5 grams of oil with the following characteristics: density @15°C = 718.5 kg/m³, distillation at 10% evaporation volume = 74.4°C, distillation at 50% evaporation volume = 123°C, and distillation at 90% evaporation volume = 142.1°C, final boiling point = 189.7°C. The first level pyrolysis process on HDPE plastic initially only produced 418 grams of oil with the following characteristics: density @15°C = 751.5 kg/m³, final boiling point = 279.4°C, distillation @200°C = 70.9%v/v. The fuel produced from the first level pyrolysis process has characteristics comparable to kerosene, while the fuel produced in the second level pyrolysis process has characteristics equivalent to 88 octane fuel.